Survey Study of Socio-Demographic Profile and Prevalence of Stress among Students of Firozabad (Uttar Pradesh) - YADAV, Dr GEETA (The journal of contemporary issues in business and government, 2021)
A cross-sectional study was carried out which was containing 430 respondents randomly sampled from students at universities, all in the age group of 18-24 years from Firozabad district. A standardized stress scale is used to measure stress. On the bases of 10 factors of stress the demographic study of stress level in university students has been done. In general, average level of stress has been observed in all students. For most of the student this study is related to educational activities to measure stress. Sometimes many types of stressors in the family, society and school inadvertently affect the students psychologically whose continuously negative effects gradually push the students towards distress. In college teachers can make aware students about the stress management and can provide various bases to reduce stress level.